O processo de implementação de programas federais de economia solidária de apoio a cooperativas de agroecologia - Mazzei, Bianca Burdini (2018)
The field of solidarity economy, as a social movement and as a public policy, is still under construction and seeks to be strengthened. In Brazil, the process of institutionalization as a federal policy began in 2003, with the creation of the National Secretariat for Solidarity Economy SENAES / MTE (Secretaria Nacional de Economia Solidária SENAES/MTE, in Portuguese), through governmental programs articulated intersectorally between different ministries. Since the beginning of the institutionalization process, the national policy of solidarity economy is presented as a development strategy and has strong ties with the agroecology production system. This way, the focus of this research is agroecology cooperatives. The process of implementing a public policy has its own complexities, which becomes even greater when it refers to a social and intersectoral policy, as is the case of the research. Thus, the objective of this research is to analyze the national policy of solidarity economy through the study of the programs implementation process to support agroecology cooperatives. The implementation process analysis used in the research considers the main elements of the top-down and bottom-up approaches, in a hybrid approach. We chose a research in an exploratory type, with a qualitative nature, and a single case study with two integrated units. The selected units are agroecological cooperatives of solidarity economy – Copavi and Cooperatvama. Its constitute the Unitrabalho field of action, of the State University of Maringá. For the data collection, an unstructured interview was used with different actors: members of cooperative management, implementing actors and actors from different government levels. Participant observation and documentary analysis were also used. Based on the public policy implementation literature and the survey of the main elements that comprise the implementation process, a specific analytical framework was developed. The implementation processes of the selected public programs to support the solidarity economy were analyzed based on this analytical framework that considers the diversity of governmental and non-governmental actors involved in the implementation process, the strategy plan drawn up by implementers to organize their actions, the existing space of discretion, and the possibilities of conflicts between the different government levels. As results, the main points of success and problems that could be used to evaluate and strengthen the field were raised.